2021
DOI: 10.1002/gj.4095
|View full text |Cite
|
Sign up to set email alerts
|

Middle Triassic lower crust‐derived adakitic magmatism: Thickening of the Dananhu intra‐oceanic arc and its implications for arc–arc amalgamation in the Eastern Tianshan (NW China)

Abstract: The timing and mechanism of the closure of the Palaeo-Asian Ocean are problematic and controversial. To help resolve these problems, we report geochronological, geochemical, and isotopic data from mid-Triassic adakitic intrusions in the Eastern Tianshan, NW China. U-Pb dating shows that the adakitic intrusions formed at 243-234 Ma. These mid-Triassic adakitic intrusions are characterized by high Sr/Y and La/Yb ratios, low Yb and Y, and positive ε Nd (t) (+3.12 − +4.71) and low ( 87 Sr/ 86 Sr) i (0.703956-0.704… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 86 publications
0
26
0
Order By: Relevance
“…As a branch of the Palaeo-Asian Ocean, the youngest closure time of the North Tianshan Ocean indicates that final amalgamation of the Palaeo-Asian Ocean occurred in Middle-Late Triassic times (Xiao et al 2015(Xiao et al , 2018Ao et al 2021;Mao et al 2021). Several stratigraphic and low-temperature thermochronological studies have recorded closure of the Palaeo-Asian Ocean.…”
Section: A Triassic-early Jurassic Coolingmentioning
confidence: 99%
“…As a branch of the Palaeo-Asian Ocean, the youngest closure time of the North Tianshan Ocean indicates that final amalgamation of the Palaeo-Asian Ocean occurred in Middle-Late Triassic times (Xiao et al 2015(Xiao et al , 2018Ao et al 2021;Mao et al 2021). Several stratigraphic and low-temperature thermochronological studies have recorded closure of the Palaeo-Asian Ocean.…”
Section: A Triassic-early Jurassic Coolingmentioning
confidence: 99%
“…(c). The geological map of the Eastern Tianshan marking the locations of Devionian to late Permian granites in the middle of the Dananhu arc in the eastern Tianshan orogen (Mao, Ao, Windley, Lü, et al., 2021; Mao, Ao, Windley, Wang, et al., 2021; Mao, Wang, Xiao, Windley, et al., 2021). The ages are listed in Table S4 in Supporting Information .…”
Section: Introductionmentioning
confidence: 99%
“…Decades of researches have shown that the Dananhu arc in the eastern Tianshan orogen is mainly an intra‐oceanic arc that was generated by subduction of the Kanguer ocean, an important branch of the Paleo‐Asian Ocean (Ma et al., 1997; Mao, Ao, Windley, Lü, et al., 2021; Mao, Ao, Windley, Wang, et al., 2021; Mao, Wang, Xiao, Windley, et al., 2021; Xiao et al., 2004; Y. Zhang et al., 2018). It experienced long‐lively complicated subduction accretionary processes from the Ordovician to the Triassic, and has discontinuous polyphase generations and types of granitic and volcanic magmatism (Figures 1b and 2; Du et al., 2019; C. M. Han et al., 2002; Lin et al., 2017; Mao, Ao, Windley, Lü, et al., 2021; Mao, Ao, Windley, Wang, et al., 2021; Q. G. Mao et al., 2019; Q. Mao et al., 2020; Mao, Wang, Xiao, Windley, et al., 2021; Sun, Wang, Wang, et al., 2019; Wang, Wang, & He 2006; Xiao et al., 2004; Y. Zhang et al., 2018; 2020; Zhou et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations